Hepatoprotective activity of the methanolic leaf extract of Moringa oleifera (Lam) against chemically-induced Liver Toxicity - Mbagwu, Herbert; Nsikan, Etok; Emem, Ekpo (International Journal of Pharmacology and Toxicology, 2016)
Aim: Moringa oleifera commonly known as â€œmiracle plantâ€ possesses enormous nutritional and medicinal properties. It is used in traditional medicine in treating many ailments, including liver disorders. Though some works on hepatoprotective effects have been done (Mishra et al., 2011), the present study aims at evaluating the methanolic leaf extract (MLE) of Moringa oleifera harvested in Ewet Housing Estate in Uyo; AkwaIbom State in South-South Nigeria.Materials and Methods: The Carbon tetrachloride (CClâ‚„) model was employed throughout this investigation (Dongare et al., 2013). Briefly, thirty animals were randomly divided into six groups of five animals in each group. Group I served as normal control and was administered 10ml/kg normal saline. Group II was the toxic control and received 3 ml/kg of CClâ‚„. Group III served as the reference control and received 100mg/kg silymarin while groups IV, V and VI received 9, 18 and 27 mg/kg of MLE respectively. Phytochemical screening, acute toxicity tests as well as free radical scavenging effects using DPPH (in vitro) were also carried out.Results: Preliminary phytochemical tests revealed the presence of tannins, flavonoids, alkaloids, anthraquinones, saponins, terpenes, phlobatanins and cardiac glycosides. The acute toxicity investigations showed that MLE LDâ‚…â‚€ was 90 mg/kg. In the hepatoprotective studies, liver function tests (LFT) revealed a significant (p<0.05) protective effect when compared with silymarin. The histopathological studies also provided supportive evidence for the protective effects of MLE. The DPPH studies showed that MLE has antioxidant property.Conclusion: It can be concluded based on findings from this study that the MLE of Moringa oleifera possesses antioxidant and hepatoprotective activities in a dose-dependent manner and safe for oral administration.